The second letter by (Mas`ar bin Muhalhal) is a historical source for the economy of the Kurdish regions - Taban Sabah Perbal (Zanco Journal of Humanity Sciences)
This paper delight the effort of one of the geographers in the fourth century AH, who is (Masaar Bin Muhalhal Al-Khazraji), he knowns as (Abu Delaf).